Lowering plasma frequency by enhancing the effective mass of electrons： A route to deep sub-wavelength metamaterials - 秦刚 王甲富 闫明宝 陈维 陈红雅 李勇峰 (Chinese physics B, 2013)
Deep sub-wavelength metamaterials are the key to the further development of practical metamaterials with small volumes and broadband properties. We propose to reduce the electrical sizes of metamaterials down to more sub-wavelength scales by lowering the plasma frequencies of metallic wires. The theoretical model is firstly established by analyzing the plasma frequency of continuous thin wires. By introducing more inductance elements, the effective electron mass can be enhanced drastically, leading to significantly lowered plasma frequencies. Based on this theory, we demonstrate that both the electric and the magnetic plasma frequencies of metamaterials can be lowered significantly and thus the electrical sizes of metamaterials can be reduced to more sub-wavelength scales. This provides an efficient route to deep sub-wavelength metamaterials and will give rigorous impetus for the further development of practical metamaterials.